Prevalence and risk factors of depression symptoms among Chinese seafarers during the COVID-19 pandemic: a cross-sectional study. Issue 6 (23rd June 2021) - Qin, Wenzhe; Li, Lei; Zhu, Dongshan; Ju, Chengfei; Bi, Pengfei; Li, Shixue
Abstract : Background: To curb the spread of COVID-19, most countries have adopted measures such as banning shore leave at ports and placed restrictions on crew change. Seafarers may bear an excess pressure during the COVID-19 pandemic. This study aimed to investigate the prevalence and risk factors associated with depression symptoms among Chinese seafarers during the COVID-19 pandemic. Design: Cross-sectional study. Methods: This field survey-based study was conducted at Rongcheng Port, Shandong Province, China, from 10 June 2020 to 25 July 2020. Sociodemographic and occupational characteristics and health-related behaviours were collected through a face-to-face questionnaire. The Self-Rating Depression Scale was used to evaluate depression status during the preceding week. Logistic regression models were used to explore factors related to depression. Results: 441 male Chinese seafarers were enrolled. Overall, the proportions of seafarers with low, moderate and severe depression symptoms were 23.35%, 9.30% and 9.07%, respectively. Compared with those with good self-rated health (SRH), seafarers with poor SRH had higher odds of depression (OR, 2.24, 95% CI 1.22 to 4.11). Less leisure time or physical exercise was associated with more severe self-reported depression symptoms (1–3 per week vs ≥4 per week: OR, 1.72, 95% CI 0.71 to 4.14; none vs ≥4 per week: OR, 3.93, 95% CI 1.67 to 9.26). Poor sleep quality was associated with higher likelihood of reporting severe depression (fair vs good: OR, 2.78, 95% CI 1.54 to 5.01; poor vs good: OR, 4.30, 95% CI 1.65 to 11.24). The more frequent seafarers worked overtime a week, the higher the likelihood of reporting severe depression symptoms (1–2 per week vs none: OR, 1.82, 95% CI 1.04 to 3.18; ≥3 per week vs none: OR, 2.49, 95% CI 1.05 to 5.92). Also, high perceived work stress was linked to higher odds of being depressed (intermediate vs low: OR, 2.06, 95% CI 0.78 to 5.46; high vs low: OR, 3.83, 95% CI 1.35 to 10.90). Conclusions: There is a high burden of depression associated with COVID-19 among seafarers. Special interventions that protect the mental health of seafarers are more critical than ever in the context of the pandemic.